Multicomponent Photocomposition as A Source for Development New Anti-Inflammatory Medicines - Khakimov Z.Z; Babazhanov A.U; Rakhmanov A.Kh; Tursunova L.I; Khadzhieva U.A (Zien Journals, 2023)
The results of experimental studies on mature white male rats showed that phytocompositions 1, 2 and 3 containing various extracts of medicinal plants have a distinct antiphlogogenic activity. Among the studied phytocollections, composition 3 showed a higher anti-inflammatory activity compared to other studied phytocollections. The studied new mixtures of medicinal plants have a higher antiphlogogenic activity than canephron, especially phytocomposition 3, and in terms of their pharmacological activity, it is not inferior to the gold standard non-steroidal anti-inflammatory drug - sodium diclofenac.
Keywords: aseptic arthritis; phytocomposition; medicinal plants